Production of hard goat cheese and goat whey from organic goat’s milk - Anka Popović-Vranješ; Ivan Pihler; Snežana Paskaš; Saša Krstović; Željka Jurakić; Katarina Strugar (Mljekarstvo)
Technology of hard goat cheese and whey production from organic goat’s milk is very complex and must be harmonized with the methods and guidelines of organic production. The organic goat cheeses are declared as products of higher quality, with greater or added value, and to achieve this, all technological parameters of production must be controlled and adapted to the desired type of cheese. In this study chemical analyses of the composition of organic and conventional goat’s milk, cheese and whey were performed. Cheese fatty acids profile was determined by gas chromatograph (GC) with FID detector, while for detection of amino acids was used HPLC method with fluorescence detection. Data obtained in the study were analyzed using Statistica 9.0 software package and significant differences were determined using t-test. Based on the results, organic milk was statistically significantly higher in all components, except in ash and sodium (p<0.05, p<0.01). Contrary, cheeses (aged 4 days) did not show significant differences (p<0.05, p<0.01), except for dry matter and lactose. During ripening of organic cheese the contents of threonine, tyrosine, valine and isoleucine decreased, whereas methionine, phenylalanine and lysine, showed a tendency to increase. Saturated fatty acids were mainly represented with myristic, palmitic and stearic acids while oleic acid was dominant as unsaturated FA. Organic whey samples contained significantly more protein (1.43 % versus 0.52 %, p<0.05, p<0.01). The application of organic standards of manufacture and control of all technological parameters in the production of organic hard goat cheese and whey resulted in obtaining a high-quality products.